Hydrogen safety effect calculation (dispersion and thermal radiation effects) for determination of siting and safe distance - Venkatesan, Rubachandran; Harun, Razif; Mohamed Yusoff, Hamdan; Abdul Razak, Musab (John Wiley and Sons Inc, 2024)
The main aim of this study was to evaluate the potential effect of dispersion, thermal radiation, and explosion from a poly-bed pressure swing adsorption (PSA) unit with its surrounding facility to determine its safety distance. Thus, the Shell FRED (fire, release, explosion, and dispersion) consequence modeling was used to predict the impact of a release scenario and assist in designing, developing, and maintaining safe operation. This study was intended to calculate dispersion contours to 50 lower flammable limit (LFL) and 100 LFL, thermal impacts of radiation flux levels of 4, 5, 12.5, and 37.5 kW/m2 at a distance, and including explosive effects of 0.1, 0.2, and 0.35 bar to the chosen target. Based on the findings, it was found that, to avoid exposure to heat radiation of 12.5 kW/m2 from the PSA unit, equipment should be located at a minimum distance of 20.84 m. Meanwhile, process modules and buildings must be located at a minimum distance of 13.8 m. The explosive nature of hydrogen makes on-site handling and storage more challenging than fossil fuels. The findings of this study will have important implications for the future handling and storage of hydrogen as a potential fuel.